GCSE intermediate maths - Crawshaw, Janet; Langley, P. (Paul) (Cheltenham : Stanley Thornes, 1999)
This title includes two books in one: a textbook and an in-built staged revision programme. It offers student-friendly revision and summary pages that really work for students. It is developed by widely respected authors. Reinforcing techniques and facts, it presents Maths 'toolbox' approach to solving problems. Support is provided for all traditionally difficult areas, as well as on-page hints and reminders to aid understanding. It also offers exam practice throughout, past questions at the end of every chapter and end-of-stage mixed exam questions to thoroughly prepare students for the exams.
Keywords: Mathematics